Isolation and Identification of a Novel Aspergillus sydowii F5 Producing a-Galactosidase and Statistical Optimization for the Enzyme Production - Cai, Guo-Lin; Lu, Jian (Asian Journal of Chemistry, 2011)
A novel strain F5, producing a-galactosidase, was isolated from Chinese wheat Qu. According to the morphological characteristics and ITS gene sequence analysis, it was identified as Aspergillus sydowii F5. Statistically based experimental designs were applied to the optimization of cultural medium for the a-galactosidase production by A. sydowii F5. Plackett-Burman design was used to evaluate the effects of variables of the fermentation medium. Among these variables, soybean meal, MgSO4 and KH2PO4 were identified to have the significant effects. Subsequently, the concentrations of soybean meal, MgSO4 and KH2PO4 were optimized using central composite design. The optimum concentration of soybean meal, MgSO4 and KH2PO4 was 22.4 g/L, 2.23 g/ L and 0.91 g/L, respectively. The optimization strategy led to a 5.1-fold increase in the a-galactosidase production.